2011
DOI: 10.1074/jbc.m111.218842
|View full text |Cite
|
Sign up to set email alerts
|

Proteins That Bind to Misfolded Mutant Superoxide Dismutase-1 in Spinal Cords from Transgenic Amyotrophic Lateral Sclerosis (ALS) Model Mice

Abstract: Mutant superoxide dismutase-1 (SOD1) has an unidentified toxic property that provokes ALS. Several ALS-linked SOD1 mutations cause long C-terminal truncations, which suggests that common cytotoxic SOD1 conformational species should be misfolded and that the C-terminal end cannot be involved. The cytotoxicity may arise from interaction of cellular proteins with misfolded SOD1 species. Here we specifically immunocaptured misfolded SOD1 by the C-terminal end, from extracts of spinal cords from transgenic ALS mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 34 publications
7
30
0
Order By: Relevance
“…Inhibition of misfolded SOD1 association with mitochondria was specific to MIF, as other chaperones tested, including Hsp27, Hsc70, aB-crystallin [previously reported to interact with mutant and misfolded SOD1 and modulate its aggregation (Karch and Borchelt, 2010; Krishnan et al, 2008; Wang et al, 2009; Wang et al, 2005; Yerbury et al, 2013; Zetterstrom et al, 2011b)], cyclophilin-A [one of our 7 candidate proteins and previously proposed to act as a chaperone (Freskgard et al, 1992)], or glutathione peroxidase [a protein with thiol-oxidoreductase activity, an activity that has been proposed to be crucial for the association of mutant SOD1 proteins with mitochondria (Cozzolino et al, 2008; Ferri et al, 2006)], had no effect on mutant SOD1 association with normal mitochondria (Figure 3F, G). …”
Section: Resultsmentioning
confidence: 92%
“…Inhibition of misfolded SOD1 association with mitochondria was specific to MIF, as other chaperones tested, including Hsp27, Hsc70, aB-crystallin [previously reported to interact with mutant and misfolded SOD1 and modulate its aggregation (Karch and Borchelt, 2010; Krishnan et al, 2008; Wang et al, 2009; Wang et al, 2005; Yerbury et al, 2013; Zetterstrom et al, 2011b)], cyclophilin-A [one of our 7 candidate proteins and previously proposed to act as a chaperone (Freskgard et al, 1992)], or glutathione peroxidase [a protein with thiol-oxidoreductase activity, an activity that has been proposed to be crucial for the association of mutant SOD1 proteins with mitochondria (Cozzolino et al, 2008; Ferri et al, 2006)], had no effect on mutant SOD1 association with normal mitochondria (Figure 3F, G). …”
Section: Resultsmentioning
confidence: 92%
“…Given the general role of Hsc70-4 in clearance of misfolded or aggregated proteins (Liu et al, 2012; Stricher et al, 2013; Zetterstrom et al, 2011), we hypothesized that Hsc70-4 OE may influence TDP-43 aggregation. To examine this, we performed subcellular fractionations from Drosophila larvae co-overexpressing wild-type or mutant TDP-43 with Hsc70-4 in motor neurons and quantified the amount of TDP-43 in the soluble (low salt, LS), sarkosyl (Sark), and urea (Urea) fractions.…”
Section: Resultsmentioning
confidence: 99%
“…5C). The misfolded mutant protein apparently exposes epitopes that are sufficiently extended and hydrophobic to recruit endogenous Hsp(c)70 in axoplasm, as occurs in vivo in mouse spinal cord (Table S1; 28,37,38). Notably, Hsc70 is the most abundant chaperone in mouse motor neurons, as revealed by laser capture microdissection and proteolysis/MS.…”
Section: Discussionmentioning
confidence: 99%
“…Blocks Slowing. Earlier studies have indicated that the molecular chaperone Hsc70 interacts with mutant human SOD1 protein in the spinal cord of transgenic mice that develop ALS (37,38). This interaction also occurred in mouse strains transgenic for G85R SOD1YFP (28).…”
Section: Inhibition Of Anterograde Fast Axonal Transport Is Abolishedmentioning
confidence: 96%